The Role of Social Media Exposure and Cultural Knowledge in Shaping Public Interest in Reog Ponorogo - Adinda Putri Wachyudi; Abdul Basit (Persepsi: Communication Journal, 2026)
Reog Ponorogo faces preservation challenges in the digital era, especially among the younger generation. This study aims to examine the role of social media exposure and cultural knowledge in shaping public interest in Reog Ponorogo culture. This quantitative explanatory research surveyed 100 respondents aged 15-25 years in Tangerang Regency using an online questionnaire. The collected data were specifically analyzed using multiple linear regression analysis. The test results prove that social media exposure and cultural knowledge, both partially and simultaneously, have a positive and significant effect on public interest. The coefficient of determination analysis confirms that the integration of these two variables explains 53.6% of the variance in public interest in preserving Reog Ponorogo. In conclusion, digital exposure and cultural understanding positively predict public interest. This study recommends regular socialization regarding healthy social media usage and cultural education as a strategic effort to preserve Indonesian culture.